Visuospatial Reasoning: An Ecocultural Perspective for Space, Geometry and Measurement Education - Owens, Kay (Springer, 2016)
This book develops the theoretical perspective on visuospatial reasoning in ecocultural contexts, granting insights on how the language, gestures, and representations of different cultures reflect visuospatial reasoning in context.